2022
DOI: 10.1001/jamanetworkopen.2022.27232
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blue Light–Filtering Intraocular Lenses With All-Cause and Traffic Accident–Related Injuries Among Patients Undergoing Bilateral Cataract Surgery in Finland

Abstract: Key Points Question Are blue light–filtering (BLF) intraocular lenses (IOLs) implanted during bilateral cataract surgery associated with improved outcomes regarding traffic accident–related injuries and driving safety? Findings In this cohort study of 4986 patients who underwent bilateral cataract surgery within the follow-up period of more than 2000 days, neither cumulative all-cause nor traffic accident–related, injury-free survival differed between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A recent study found that 9/80 (11%) patients with BLF IOLs complained of glare issues while driving at night compared with 0/83 patients with UV-only IOLs. 32 Such results are hard to interpret, and it is not clear, mechanistically, how a filtering lens would increase the perception of glare; previous studies that measured driving safety found that BLF IOLs improved driving under glare conditions. 29 , 33 The perception of glare might be due to a negative effect of BLF on scotopic functioning.…”
Section: Blue Light Filtration and Visual Functionmentioning
confidence: 99%
“…A recent study found that 9/80 (11%) patients with BLF IOLs complained of glare issues while driving at night compared with 0/83 patients with UV-only IOLs. 32 Such results are hard to interpret, and it is not clear, mechanistically, how a filtering lens would increase the perception of glare; previous studies that measured driving safety found that BLF IOLs improved driving under glare conditions. 29 , 33 The perception of glare might be due to a negative effect of BLF on scotopic functioning.…”
Section: Blue Light Filtration and Visual Functionmentioning
confidence: 99%
“…-may be beneficial as part of the treatment of amblyopia, 26 -improve mood and sleep quality, 28 -may be used as an additive treatment for patients with sleep disturbances in the course of psychiatric disorders, 13,30 -may lead to better reading capacity in children with reading difficulties. 27 -no influence on contrast vision or visual acuity, [17][18][19][20] -do not reduce symptoms of DES, 36,37 -might dysregulate the circadian rhythm, 36 -do not influence mental symptoms and psychiatric disorders in patients after cataract surgeries, 38,39 -do not reduce number of injuries in patients after cataract surgeries, 40 -do not prevent development of AMD. [45][46][47][48] The impact of BB filters on vision and reading Many studies investigated the influence of BB filters on visual function.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…39 Another study proved that the use of BB IOLs did not reduce the number of injuries and patients with BB IOLs had a worse glare during driving at nighttime, but that did worsen the comfort of driving. 40 Another assessed factor was the influence of BB IOLs on the thickness of the retinal nerve fiber layer (RNFL), and a clinical trial by Kim et al proved, that BB IOLs did not influence the RNFL after cataract surgery, so there is no additional benefit of using these types of lenses. 41 Also, the type of used lenses does not affect the development of inflammation connected to cataract surgery.…”
Section: The Impact Of Bb Filters On Patients After Cataract Surgeriesmentioning
confidence: 99%
“…12 Our previous study has shown that BLF IOLs were not associated with reduced risk of injuries or driving accidents, whereas glare during nighttime driving was significantly worse in the BLF IOL group with pseudophakia. 13 Bluelight can also negatively affect retinal ganglion cell function which is particularly important in glaucoma. 14,15 Previous studies have suggested that phacoemulsification cataract surgery with implantation of clear (non-BLF) IOLs may lead to improvement in depressive symptoms and the number of health contacts for depression and/or anxiety.…”
mentioning
confidence: 99%
“…12 Our previous study has shown that BLF IOLs were not associated with reduced risk of injuries or driving accidents, whereas glare during nighttime driving was significantly worse in the BLF IOL group with pseudophakia. 13 Blue-light can also negatively affect retinal ganglion cell function which is particularly important in glaucoma. 14,15…”
mentioning
confidence: 99%